Nutritional Development and Sensory Evaluation of Pumpkin and Corn Grits for Pregnant Women - Zatira, Sarah; Ahmad, Aripin; Rachmawati, Rachmawati; Andriani, Andriani (JAND: Journal of Applied Nutrition and Dietetic, 2025)
The incidence of chronic energy deficiency (CED) in pregnant women remains high. One of the interventions is the utilization of local supplementary foods, though options such as pumpkin and corn remain limited. Purpose: This study aimed to determine the effect of adding pumpkin to the acceptability and proximate composition of pumpkin-corn grits. This was an experimental study using a completely randomized design (CRD) with 3 treatments and 3 replications. Data were analyzed using ANOVA and Duncan’s multiple range test. The addition of 40g, 50g, and 60g of pumpkin significantly affected organoleptic properties, particularly taste (p < 0.05), with average panelist scores ranging from 3.13 to 3.68 (liked category). No significant differences were found in color, aroma, or texture. The highest values for water, ash, and protein content were observed in the F3 treatment (60g pumpkin), while the highest fat, fiber, and carbohydrate contents were found in F1 (40g pumpkin). The acceptability test showed significant differences in color, taste, aroma, and texture for the F3 formula (p < 0.05). The addition of pumpkin significantly improved taste and affected proximate values for ash, fat, and protein. Local governments and health programs may consider using pumpkin-corn grits as an alternative supplementary food for pregnant women.